Literacy Acceleration: Interactive Learning Through Fairy Tale Video Shows Using Technology Adaptation in Elementary School Education: Akselerasi Literasi: Pembelajaran Interaktif Melalui Tayangan Video Dongeng Menggunakan Adaptasi Teknologi di Pendidikan Sekolah Dasar - Crismono, Prima; Agustin Reni Pitasari, Mely; Hanifiyah, Fitriyatul; Febriyanti, Beby (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2024)
Interactive learning of fairy tale videos through technology adaptation is a strategy to instill interest in literacy by using technology. Rapid advances in technology are used as an instrument to accelerate literacy. This research is a form of implementing innovation in the use of technology to create interesting learning methods. The focus of this research explains how students can later make literacy a positive habit in everyday life. Literacy education is the basic key to exploring science, presented through showing fairy tale videos. Activities are structured based on a theoretical framework regarding the stages in realizing an education acceleration program. The research method used is a qualitative method by conducting Focus Group Discussions (FGD) and observation. Research data was obtained from 3 elementary schools in Arjasa-Sukowono Village. The research results show that the use of technology for learning has a positive impact on students. With digital learning innovation, students become more interactive, can generate analytical skills regarding the essence of values ​​and awaken imaginative power. This activity can be used as a reference for future literacy curriculum and implemented on an ongoing basis for educators in related agencies.